Identification of novel linear epitopes in P72 protein of African swine fever virus recognized by monoclonal antibodies - Yin, Dan; Geng, Renhao; Shao, Hongxia; Ye, Jianqiang; Qian, Kun; Chen, Hongjun; Qin, Aijian (Frontiers in Microbiology, 2022)
African swine fever (ASF) is one of the highly contagious and lethal diseases among domestic pigs and wild boars. The capsid protein P72 of African swine fever virus (ASFV) is very important for the diagnosis and vaccine development. However, the epitope of the protein is not clear. In this study, capsid protein P72 was expressed in Sf9 cells along with its chaperone B602L. A total of ten monoclonal antibodies (mAbs) specific to P72 protein were developed by fusions between SP2/0 cells and spleen cells of mice immunized with the recombinant-P72&B602L proteins expressed in Sf9 cells. Four liner B cell epitopes 31SNIKNVNKSY40, 41GKPDP45, 56HLVHFNAH63 and 185ERLYE189 were identified. Biological information analysis illustrated that epitopes 31SNIKNVNKSY40, 41GKPDP45 and 185ERLYE189 were highly conserved within different ASFV strains. These findings may lead to a better understanding of the antibody-antigen interaction and provide new insights into the vaccine research and serological diagnosis of ASF.